2018
DOI: 10.1029/2018ja025846
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Study of Phase Relationship Between Magnetic and Plasma Pressures in the Near‐Earth Nightside Magnetosphere Using the THEMIS‐E Satellite

Abstract: Distributions of plasma and magnetic pressures are the basic information to investigate macroscopic dynamics of the Earth's magnetosphere. Several studies have been made on magnetic and plasma pressures and macroscopic plasma instabilities in the magnetosphere. However, correlation between magnetic and plasma pressure variations has not been statistically investigated. In this paper, we analyze the statistical characteristics of the phase relationships between variations of magnetic and plasma pressures at fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Shiokawa et al (2010), Shiokawa et al (2014), and Hashimoto et al (2015) have reported auroral finger-like structures mainly in the post-midnight local times at the equatorward part of the auroral oval. These auroral finger-like structures are likely to be caused by the pressure-driven instability with the anti-phase variation of magnetic and plasma pressures (Nishi et al, 2017(Nishi et al, , 2018 and are possibly accompanied by ambient density structures. Ebihara et al (2010) have reported highly structured thin auroras near the equatorward edge of the auroral oval.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Shiokawa et al (2010), Shiokawa et al (2014), and Hashimoto et al (2015) have reported auroral finger-like structures mainly in the post-midnight local times at the equatorward part of the auroral oval. These auroral finger-like structures are likely to be caused by the pressure-driven instability with the anti-phase variation of magnetic and plasma pressures (Nishi et al, 2017(Nishi et al, , 2018 and are possibly accompanied by ambient density structures. Ebihara et al (2010) have reported highly structured thin auroras near the equatorward edge of the auroral oval.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Highly anisotropic plasmas can also be unstable to (drift‐) mirror modes (e.g., Génot et al., 2001; Hasegawa, 1969), also characterized by anticorrelated magnetic field and density. Statistical studies of the outer magnetosphere often attribute observed anticorrelations to this mode, despite the instability criterion not always being satisfied (Nishi et al., 2018; Vaivads et al., 2001; Zhu & Kivelson, 1991, 1994). Magnetopause surface waves might account for some of these observations.…”
Section: Discussionmentioning
confidence: 99%
“…Similar situations have been reported in many events in the magnetosphere (Korotova et al., 2009; Vaivads et al., 2001; X. Zhu & Kivelson, 1994) and sometimes even in the magnetosheath (Balikhin et al., 2009). Although some studies about compressional ULF waves with the antiphase relation stated that the ULF waves were not consistent with the mirror mode because the condition of the mirror instability was not satisfied (Nishi et al., 2018; Takahashi, Fennell et al., 1987), once a mirror mode structure is generated by the instability, the structure would not collapse soon even if the surrounding environment changes to the condition under which the mirror instability cannot grow. Statistical studies of mirror mode structure in the magnetosheath showed that there are significant numbers of mirror mode like structures that do not satisfy this condition (Génot et al., 2009; Soucek et al., 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Statistical studies by X. Zhu & Kivelson (1991) and Nishi et al. (2018) showed that many magnetospheric compressional ULF waves have an antiphase relation between the magnetic and ion pressures. Based on event studies, such compressional ULF waves in the magnetosphere are thought to be generated by the drift mirror instability in many cases because of the antiphase relation and/or their small phase velocities in the plasma rest frame (e.g., Baumjohann et al., 1987; Constantinescu et al., 2009; Korotova et al., 2009; Lanzerotti et al., 1969; Rae et al., 2007; Soto‐Chavez et al., 2019; Takahashi, Lopez et al., 1987; Vaivads et al., 2001; X. Zhu & Kivelson, 1994).…”
Section: Introductionmentioning
confidence: 99%